Performance improvement of turbo energy recovery device in desalination using flow field simulation and uniform design experiment - Shenghui Wang; Yexiang Xiao; Chengpeng Wang; Yuhai Li; Qingfen Ma; Xianwu Luo (Desalination and Water Treatment)
As the core equipment of seawater desalination, the turbine energy recovery device (TERD) exerts a crucial impact on the energy consumption of desalination system. The study aims to improve the performance of TERD mainly using the numerical simulation. The internal flow field characteristics of TERD under different working conditions are thoroughly analyzed by the 3D model. The key performance indicators of the test platform are optimized and improved via the carefully designed experimental scheme and the principle of vortex dynamics. The results show that although the flow dominated by vortices is weakened on both sides of TERD, a significant flow loss occurs in the impeller and baffle area due to the increase of the number of vortices. The vortices are mainly derived from the opposite vortex flow direction in the annular section of the volute. Further research shows that the blade placement angle plays an important role in the turbine side and pump side performance of TERD. After optimization, the efficiency of TERD increases by 11.14 %, which effectively reduces the dependence on energy, thereby reducing its cost input in practical application scenarios and providing a strong guarantee for the efficient and stable operation of TERD in seawater desalination.